2001
DOI: 10.1902/jop.2001.72.6.722
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dehiscences and Fenestrations in Modern American Skulls

Abstract: The presence of dehiscences and fenestrations were positively correlated with thin alveolar bone and negatively correlated with occlusal attrition. African-American males and Caucasian females were significantly more likely to have dehiscences, while African-American females were significantly more likely to have fenestrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
99
1
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(116 citation statements)
references
References 15 publications
11
99
1
5
Order By: Relevance
“…Besides, the high prevalence of alveolar fenestrations and dehiscences were found in skull studies. 1,2 Loss of periodontal support tissue will lead to loosening of the teeth and affect oral function, while conventional periodontal surgical approaches such as root surface conditioning or guided tissue regeneration result in limited new bone, cementum, and periodontal ligament formation. Moreover, the formation of new bone and cementum with supportive periodontal ligament is the ultimate objective for periodontal tissue regeneration, but current regeneration therapies are incapable of achieving this in a predictable way.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the high prevalence of alveolar fenestrations and dehiscences were found in skull studies. 1,2 Loss of periodontal support tissue will lead to loosening of the teeth and affect oral function, while conventional periodontal surgical approaches such as root surface conditioning or guided tissue regeneration result in limited new bone, cementum, and periodontal ligament formation. Moreover, the formation of new bone and cementum with supportive periodontal ligament is the ultimate objective for periodontal tissue regeneration, but current regeneration therapies are incapable of achieving this in a predictable way.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, in addition to the ability to differentiate into osteoblast-like cells and adipocytes, PDLSCs can also specifically differentiate into periodontal cells, such as cementoblast-like cells and collagen forming cells in vitro, and they possess the capacity to generate a cementum/PDL-like structure when they were transplanted into nude mouse and preclinical periodontal defect models. [5][6][7][8][9][10][11][12] Conventional hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 , HA) bioceramics had been used in periodontal bone tissue repair for their chemical similarity to bone mineral and their excellent biological activity and osteoconductivity. 13 However, it is reported that HA bioceramics lack osteoinductive ability, and consequently possess limited ability to form an interface with new bone tissue and hence hamper the new bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…Dehiscence and fenestration presence were also identified on the 30 koala skulls according to the methods of Rupprecht (2001) and Tal (Tal, 1983). On the birooted or unirooted teeth, only the buccal or lingual/palatal surfaces were examined.…”
Section: Dehiscences and Fenestrationsmentioning
confidence: 99%
“…9 One study showed that 40% of American skulls had at least one dehiscence, with 67% of dehiscences in the mandible. 10 Mostofa et al 11 performed anterior mandibular flaps and CBCTs on 32 patients. Seventy-eight percent of patients had at least one dehiscence, and the highest rates were seen on the canines.…”
Section: Introductionmentioning
confidence: 99%